Optimalisasi Kecerdasan Buatan untuk Pendidikan Islam Berkarakter : Model Implementasi dan Dampaknya pada Generasi Muda - Nova Yanti (Reflection : Islamic Education Journal, 2024)
This study aims to explore the use of artificial intelligence (AI) in Islamic character education, focusing on the implementation of the model and its impact on the younger generation. The background of this study is based on the increasing need to present innovative solutions in education that not only meet academic aspects but also develop students' characters in accordance with Islamic values. The research method used is a qualitative approach with in-depth interview techniques and participatory observation in several Islamic educational institutions. The results of the study indicate that the application of AI in learning increases student engagement and personalizes the learning experience, thereby helping to develop better character. In addition, this study found that despite challenges in presenting content that is in accordance with Islamic principles and infrastructure limitations, the effective application of AI can create a learning environment that supports educational characters that are relevant to the challenges of the 21st century.